The vasodilatory effect of acupuncture and medicine-cake-separated moxibustion on a 28-year course of Takayasu arteritis: a case report - Wang, Zheqi; Sang, Gao; Lin, Feijin; Liu, Yingjun (Frontiers in Cardiovascular Medicine, 2025)
IntroductionLarge vessel vasculitis (LVV) is a complex inflammatory condition that primarily affects large blood vessels, leading to stenosis or occlusion and thereby disrupting normal blood flow. This case study presents a 71-year-old female Asian patient who experienced recurrent dyspnea and generalized fatigue since 1996 and was diagnosed with Takayasu arteritis (TAK) in 2000. Despite undergoing multiple interventions, her symptoms persisted. In 2008, she began treatment with acupuncture and medicine-cake-separated moxibustion. Specific local and distal acupoints were targeted, and moxibustion with earthworm powder cakes was applied, using 3–5 moxa cones per session. Significant improvements in fatigue and dyspnea were observed following three treatment sessions. Over half year period of continuous treatment, the patient experienced complete resolution of symptoms, including the return of the previously non-palpable left radial pulse. Imaging studies conducted in 2009, 2011, 2016, 2019, and 2022 showed increased blood flow in the left common carotid artery and the development of collateral circulation, along with symptom relief, thus confirming the stability of the condition.Case summaryThis case study describes a female Asian patient, born in 1953, who experienced dyspnea and fatigue since 1996 and was diagnosed with TAK in 2000. She commenced treatment in 2008, which comprised acupuncture and medicine-cake-separated moxibustion. Following six courses of treatment, significant improvements in fatigue and dyspnea were noted. During the 14-year follow-up period, the patient experienced near-complete resolution of symptoms.ConclusionThis study underscores the significant improvement and sustained post-treatment effects of acupuncture combined with moxibustion using a separated medicine cake in managing late-stage LVV.